The Digital Socialization Effectiveness of “Destroy The Illegal Cigarettes” at Customs and Excise Office in Surakarta - Sunardiyah, Fina; Pawito, Pawito; Naini, Albert Muhammad Isrun (JURNAL KOMUNIKASI INDONESIA, 2023)
Circulation of illegal cigarettes is a crucial issue in Indonesia and getting worse during the Covid-19 Pandemic. Illegal cigarettes are an alternative solution because legal cigarettes are too expensive. The high price of legal cigarettes caused by government regulation on excise duty. Public’s understanding about the bad effects of cigarettes needs to be improved, because the health expense caused by smoking is much higher than the excise on tobacco products. Based on this problem, this study aims to analyze the effectiveness strategy of The Customs and Excise Office in Surakarta in suppressing the circulation of illegal cigarettes through digital socialization. This type of research is qualitative research and uses a qualitative research design, data collection techniques in this research are observation, interviews and documentation. The research result shows that the implementation of digital socialization by the Surakarta Customs and Excise to suppress the circulation of illegal cigarettes is already effective. Digital-based socialization is a suitable strategy in disseminating persuasive information. The consideration of the socialization strategies success of the Surakarta Customs and Excise is supported by informants’ opinions who say that education is an important aspect that can support the society’s understanding about illegal cigarettes. The development of technology and information makes information dissemination access easier and unlimited. The digital socialization is done with educational poster media, traditional performing arts held virtually, educational video published through digital platforms proved effective referring to the total content views which are more than expected. Socialization needs to be improved furthermore.